STRATEGI KOMUNIKASI ORGANISASI KETUA KARANG TARUNA TUNAS MEKAR DALAM EVENT TUNAS MEKAR CUP IV - Munawwar Aldy, Fakhrudi; Sekar Wangi, Maya; Mahar Rizqi, Fikriana (Solidaritas, 2024)
Every activity in an organization whether or not communication activities are effective is largely determined by communication strategy, strategy is essentially planning (planning) and management (management) to achieve a goal.The purpose of this research is to see the organizational communication strategy of the Head of Tunas Mekar Youth Organization in the Tunas Mekar Cup IV event.This research uses the theory of organizational communication strategy. Types and methods of research using primary data from interviews and secondary data from documents, books, and journals. The data collection technique used is Purpose Sampling, while to test credibility using Triangulation of Sources and analyzed by the interactive analysis method developed by Mattew B. Milles and A. Michel Huberman. Milles and A. Michel Huberman, namely data condensation, presenting data, then drawing conclusions or verification. In running an event Tunas Mekar Cup IV requires stages of communication strategy, namely strategy formulation, strategy implementation, and strategy evaluation. In the strategy formulation, researchers use communication strategy planning to achieve success. In planning the communication strategy itself using the planning model from Cangara Hafied, namely, the â€œSign Flow Communication Planning Modelâ€. In the target team selected must have high quality and loyalty. Organizing the Tunas Mekar Cup IV event is based on the initial goal of providing a forum for the younger generation and providing entertainment to the community. The messages used are persuasive and informative messages. Building commitment to the Tunas Mekar Cup IV event still uses previous values and techniques and increases commitment. Selection and use of media in delivering messages with online media and print media. Making a communication plan can be by direct negotiation, the concept of the media used, licensing of related parties, proposals for sponsors and donors, evaluation of success. In the implementation of communication strategies in the Tunas Mekar Cup IV event requires collaboration between parties. The chairman overcomes member problems by taking a personal approach to members who run away from the assigned tasks. The success of the Tunas Mekar Cup IV event can be obtained by all committee members doing their duties and responsibilities well. Evaluation of the communication strategy of Tunas Mekar Youth Organization is done by forming a group discussion forum (FGD) and evaluating individual and team performance. The conclusion of this research is that the communication strategy of the Head of Tunas Mekar Youth Organization in the Tunas Mekar Cup IV event can be said to be not in accordance with expectations, but in its implementation it is still running smoothly. Keywords: Organizational Communication Strategy, Stages of Communication Strategy, Youth Organization, Sign Flow Planning Model,